Social democracy and communism betrays the revolution the Spanish revolution - Berneri, Camillo
"Camillo Berneri DIGITAAL TE RAADPLEGEN IN DE LESESZAALUit : 'Guerra di Class' No. 8, 1st February, 1937. Vertaling gepubliceerd in 'The Cienfuegos Press Anarchist Review' Number 4, 1978Zie CD-ROm 'Anarchy is Order'"